2016
DOI: 10.1063/1.4965301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear standing wave and acoustic streaming in an exponential-shape resonator by gas-kinetic scheme simulation

Abstract: Nonlinear standing waves and acoustic streaming in an axial-symmetrical resonator with exponentially varying cross-sectional area were studied. A two-dimensional gas-kinetic Bhatnagar-Gross-Krook scheme based on the non-structure triangular grid was established to simulate nonlinear acoustic oscillations in the resonator. Details of the transient and steady flow fields and streaming were developed. The effects of winding index of the exponential-shape resonator, the displacement amplitude of the acoustic pisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These results also show that, for the exponential tube, the optimal shape parameter was 2.2, with which the highest value of the pressure amplitude can be produced. An earlier study [29] also revealed that the m = 2.2 exponential tube has a better energy-gathering ability and shock-suppression effect.…”
Section: Validation Of the Modelmentioning
confidence: 86%
See 3 more Smart Citations
“…These results also show that, for the exponential tube, the optimal shape parameter was 2.2, with which the highest value of the pressure amplitude can be produced. An earlier study [29] also revealed that the m = 2.2 exponential tube has a better energy-gathering ability and shock-suppression effect.…”
Section: Validation Of the Modelmentioning
confidence: 86%
“…In past decades, with the development of mesoscopic methods, the gas-kinetic scheme (GKS) has been widely used to study the compressible fluid flow, heat transfer, turbulent flow, hypersonic, and non-linear acoustic problems [23][24][25][26][27][28][29][30][31], etc. Xu et al [23,24] developed and continually improved the multidimensional gas-kinetic Bhatnagar-Gross-Krook (BGK) scheme to improve its favorable properties in capturing discontinuities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations